Body Shaming and Adolescent Mental Health: Implications for Guidance and Counseling Practice - Putri Happy Hapsari; Rosada Rosada; Anggia Evitarini (Journal of Behavioral Innovation, 2026)
This study aims to examine the impact of body shaming on adolescent mental health and its implications for guidance and counseling at SMK Kesuma Bangsa 2 Depok. A quantitative research approach was employed using a survey method. The participants of this study consisted of 138 students from grades X, XI, and XII in the 2024/2025 academic year. Data were collected using questionnaires and analyzed through prerequisite tests and simple linear regression analysis. The results showed that body shaming has a significant effect on adolescent mental health. The coefficient of determination (R²) was 0.340, indicating that body shaming contributes 34% to variations in students’ mental health, which falls into the moderate category. Furthermore, the correlation coefficient (r) of 0.304 also indicates a moderate relationship between body shaming and adolescent mental health. These findings suggest that body shaming plays a meaningful role in influencing adolescents’ mental health. Therefore, guidance and counseling services are essential in addressing this issue by providing preventive and interventive programs to support students’ psychological well-being.